Effects of estrogen on calcium signaling in molecular pathways of pain; Importance of TRPV1 cation channels - YAZĞAN, Yener; YAZĞAN, Betül (Zenodo, 2024)
Abstract Pain is an unpleasant and uncomfortable sensation that informs us that something is wrong and overrides other neuronal signals. Nociceptive pain is an unconscious response of sensory receptors to noxious stimuli. Transient Receptor Potential (TRP) channels are a family of non-selective cation channels located at nociceptive sensory nerve endings that respond to thermal, mechanical, or chemical stimuli with threatening/irritating potential. Depending on the type and intensity of the stimulus, different TRP proteins alter calcium ion permeability and modulate cellular response patterns. TRP Vanilloid Receptor-1 (TRPV1), which has the most crucial role in the activation of pain transmission pathways in this family, is sensitive to vanilloid-like chemicals, temperature (>430C), and low pH. Recent studies indicate that gonadal hormones are actively involved not only in reproductive behavior and sex determination but also in all physiological systems. Current literature shows that gonadal hormones play active roles not only in reproductive behavior and sex determination but also in all physiological systems. Estrogen, the most potent of these hormones, has been the subject of numerous studies due to its vital effects on the nervous system, such as neuronal viability, excitability, and perception of somatosensory stimuli. Although the literature shows that estrogen has essential roles in the modulation of pain, there is insufficient evidence regarding the molecular pathways of its effect. This review aims to investigate the importance of calcium signaling in the molecular pathways of pain and the effects of estrogen on TRPV1 cation channels that alter the calcium ion permeability of nociceptors.   Keywords: TRPV1 channels; Estrogen; Calcium; Pain; Nociceptors
Keywords: 3. Good health